PENGGUNAAN INSTAGRAM SEBAGAI MEDIA KOMUNIKASI DALAM MENINGKATKAN KONSUMEN LAUNDRY SEPATU D’SHOES CARE BEKASI - Dede Sulaeman; Muhammad Alfansa Frantana (Interpretasi: Communication & Public Relations, 2022)
Marketing communication is a process that involves two parties, namely the company (Shoes Laundry D'Shoes Care Bekasi) and the customer (Consumer), not only that but also defined as how to establish a good relationship with the customer and create value for the customer. Where this value will be good assessment/feedback from customers in order to increase or get profit for the company, namely D'Shoes Care Bekasi which is a company engaged in cleaning/laundry services. Researchers carry out this research using a post-positivist paradigm. The method used in this research is a qualitative descriptive method, research that intends to investigate the conditions, circumstances, existence, and other things that have been mentioned before and then explained again through a report form. The purpose of this research is to explain the use of Instagram as a marketing medium in increasing sales. The data in this research were obtained by means of in-depth interviews, observation, and direct research on the field, so the results obtained in this research shows indicate that the use of Instagram as a marketing medium is quite successful in increasing product or service sales.